SYMBOLIC REPRESENTATIONS: A STUDY OF CHINUA ACHEBE’S ARROW OF GOD AND ALEX LA GUMA’S A WALK IN THE NIGHT. - Udjo-Igboh, Voke (EBSU Journal of Social Sciences and Humanities, 2024)
It is unquestionably true that many literary writers employ symbols, signs, images and imagery to express profound connotations that are beyond the surface implications of their work. Symbolism has become a vital concept that is used not just in our everyday life but also in literature to represent or express qualities and ideas. It is a communicative style that involves the application of the signifier and the signified. The research is anchored on the theoretical foundation known as Semiotics and Symbolic Interactionism. The study examines and critically evaluates symbols and meaning in these novels. These authors make use of multiple symbols that have deeper meaning in their novels. For instance, in Achebe’s Arrow of God, he uses signifiers like ‘Nzu’-Chalk as a token of goodwill. ‘Kolanut’ among the Ndi-Igbo is used by hosts to welcome visitors into their homes. In Alex La Guma’s A Walk in the Night, images of dirt, filth and ugliness represent the physical environment and the direct reflection of the mental, physical and moral qualities of the characters. At the end of this research, it is discovered that several authors always use symbols to express their ideas and opinions in symbolic ways that are beyond the written words.